2021
DOI: 10.4240/wjgs.v13.i8.859
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on presentation, management, and outcomes of acute care surgery for gallbladder disease and acute appendicitis

Abstract: BACKGROUND The ongoing coronavirus disease 2019 (COVID-19) pandemic has significantly disrupted both elective and acute medical care. Data from the early months suggest that acute care patient populations deferred presenting to the emergency department (ED), portending more severe disease at the time of presentation. Additionally, care for this patient population trended towards initial non-operative management. AIM To examine the presentation, management, and outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 30 publications
1
20
0
2
Order By: Relevance
“…Furthermore, a significant increase in delayed medical treatment for various emergencies during the COVID-19 pandemic period has been noted [ 13 , 14 ]. Several recent studies of acute appendicitis during COVID-19 pandemic clearly show that staying at home due to public health safety orders negatively impacted children and adults who developed appendicitis [ 6 , 10 , 13 15 ]. During the COVID-19 pandemic, an increased rate of perforated appendicitis, compared to the pre-COVID-19 period, was reported in several published studies [ 6 , 10 , 14 , 16 – 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a significant increase in delayed medical treatment for various emergencies during the COVID-19 pandemic period has been noted [ 13 , 14 ]. Several recent studies of acute appendicitis during COVID-19 pandemic clearly show that staying at home due to public health safety orders negatively impacted children and adults who developed appendicitis [ 6 , 10 , 13 15 ]. During the COVID-19 pandemic, an increased rate of perforated appendicitis, compared to the pre-COVID-19 period, was reported in several published studies [ 6 , 10 , 14 , 16 – 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies of acute appendicitis during COVID-19 pandemic clearly show that staying at home due to public health safety orders negatively impacted children and adults who developed appendicitis [ 6 , 10 , 13 15 ]. During the COVID-19 pandemic, an increased rate of perforated appendicitis, compared to the pre-COVID-19 period, was reported in several published studies [ 6 , 10 , 14 , 16 – 18 ]. Moreover, it has been noted that patients with perforated appendicitis have had an increased rate of complications and length of hospital stay [ 3 , 11 , 12 , 17 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1,333 patients were studied before and 1,235 after the onset of the pandemic. Four studies reported numbers in all three different approaches regarding acute cholecystitis management and are therefore examined together ( 13 , 15 , 16 , 23 ). Combining the results of these studies, 344 patients were examined before and 497 during the COVID-19 period.…”
Section: Resultsmentioning
confidence: 99%
“…Surgical management was reported in 215 patients (62.5%) before and 275 (55.3%) during the pandemic. One study showed a relative increase in the number of PCs performed during the COVID-19 period ( 23 ). These results indicate that throughout the pandemic, there has been a slide tendency toward conservative management, whereas the surgical approach is less considered compared to the pre-COVID-19 period.…”
Section: Resultsmentioning
confidence: 99%